The Role of Manufacturing Strategies and Environmental Hostility as Moderators of Technology-Overall Performance Relationship - Lena Ellitan (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
Technology is hardware and or software employed to solve operational problems effectively in an or-ganization The fact that technology is a potential source of competitive advantage is widely accepted in management and economic literature. Technology adoption creates competitive opportunities and threats for those who adopt them and for those who did not. Although there have been many studies focusing on the determinants of technological adoption and innovation, there is still a dearth of empirical results that relate to technology adoption and performance, especially in the Indonesian manufacturing sector. Based on the findings of the previous studies, the increased used of advanced manufacturing technologies and new management practices cannot be directly related to higher performance, this study try to integrate technological and innovation considerations with manufacturing strategic development. This study focused on the role of manufacturing strategy and environmental hostility in moderating the impact of hard and soft technology on overall performance. The alignment between technology and manufacturing strategy is necessary to ensure success of firms. Data were collected through mailed questionnaires. Respondents were CEOs of medium and large manufacturing firms on Indonesia. The questionnaires were sent to 1000 CEOs manufacturing firms, an 18.41% response rate. Test of non-response bias indicated that the sample is representative for this study. This study finds that both hard and soft technologies have positive impacts on overall firm’s performance. Further, manufacturing strategy and environmental hostility play an important moderating role on the relationship between technology and performance. Keywords: performance, environmental hostility, manufacturing technologies